2009
DOI: 10.7589/0090-3558-45.3.653
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of White-Tailed Deer Fawns (Odocoileus Virginianus) With Bovine Viral Diarrhea Virus Type-1 Isolated From Free-Ranging White-Tailed Deer

Abstract: ABSTRACT:The objective of the current study was to elucidate the within-host dynamics of bovine viral diarrhea virus (BVDV) type-1 infection to better understand how this virus could be maintained in white-tailed deer (Odocoileus virginianus, WTD) populations. The BVDV type-1 used in this study was originally isolated from a free-ranging WTD in Indiana. Four fawns were intranasally inoculated with 2 ml BVDV type-1 strain 544 WTD at a 10 6 tissue culture infectious dose (TCID 50 )/ml. Two fawns were inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 26 publications
3
21
0
Order By: Relevance
“…Lower than expected antigen expression in lymphoid tissues likely resulted from the often severe lymphoid depletion observed in Peyer's patches, thymus and lymph nodes. Prominent lymphoid depletion was also detected in a previous description of PI white-tailed deer (Duncan et al, 2008a) and whitetailed deer fawns following acute experimental infection (Raizman et al, 2011). While decreases in circulating lymphocytes and lymphoid depletion are common in acutely infected cattle, lymphoid depletion is not a common feature in PI cattle, contrasting with the findings in deer (Walz et al, 2001;LieblerTenorio et al, 2002LieblerTenorio et al, , 2004.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Lower than expected antigen expression in lymphoid tissues likely resulted from the often severe lymphoid depletion observed in Peyer's patches, thymus and lymph nodes. Prominent lymphoid depletion was also detected in a previous description of PI white-tailed deer (Duncan et al, 2008a) and whitetailed deer fawns following acute experimental infection (Raizman et al, 2011). While decreases in circulating lymphocytes and lymphoid depletion are common in acutely infected cattle, lymphoid depletion is not a common feature in PI cattle, contrasting with the findings in deer (Walz et al, 2001;LieblerTenorio et al, 2002LieblerTenorio et al, , 2004.…”
Section: Discussionsupporting
confidence: 55%
“…Among freeranging species, BVDV infections of white-tailed deer have recently received much attention. The virus was identified in free-ranging white-tailed deer Duncan et al, 2008a;Passler et al, 2008;Pogranichniy et al, 2008) and experimental infections resulted in clinical signs analogous to those in cattle (Ridpath et al, 2007(Ridpath et al, , 2008Raizman et al, 2009). White-tailed deer can become persistently infected with BVDV and shed the virus at similar levels to cattle , which can result in efficient transmission to other deer (Passler et al, 2009a).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In wild ruminants, pestivirus pathology is poorly known. Experimental infection with BVDV has been carried out in white-tailed deer (Odocoileus virginianus; Passler et al, 2007;Ridpath et al, 2007;Duncan et al, 2008;Raizman et al, 2009), elk (Cervus elaphus; Tessaro et al, 1999), and mule deer (Odocoileus hemionus; Van Campen et al, 1997). In most of these studies, no clinical signs were reported while abortion, fever, and lymphocyte depletion were described in others (Duncan et al, 2008;Raizman et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Persistent infection and histopathologic lesions have been well documented in wild ungulates, especially in mule and whitetailed deer fawns and adults (Duncan et al, 2008a, b;Ridpath et al, 2008;Passler et al, 2009;Raizman et al, 2009). However, in pregnant white-tailed deer the pathogenesis of transplacental BVDV infection is still incompletely understood.…”
mentioning
confidence: 99%